The Interaction Mechanisms of Swimming Biomimetic Fish Aligned in Parallel Using the Immersed Boundary Method - Xiaowei Cai; Tonghua Xu; Jun Zhang; Yanmei Jiao; Haiyang Yu (Journal of Marine Science and Engineering)
In natural environments, fish almost always swim in groups. Investigating the coupled mechanism of biomimetic fish exhibiting autonomous swimming capabilities advances our understanding of fish schooling phenomena and simultaneously aids in refining the structural and formation configurations of underwater robotic vehicles. This work innovatively develops an algorithm based on the Direct-Forcing Immersed Boundary Method (DF-IBM) and implements it in an efficient, modular software program written in C++. The program accelerates the calculation process by using a multigrid method. Validation against a benchmark case of flow around a cylinder, with comparison to data from the existing literature, verifies the program’s precision with discrepancies of less than 3.6%. Based on this algorithm, the paper analyzes the incompressible viscous flow during the movement of parallel-aligned biomimetic fish. It uncovers the interaction between the fish’s motion and the surrounding flow field and also reveals the hydrodynamic mechanisms of the group motion of the parallel-aligned biomimetic fish. The flow field under varying spacing and phases between the parallel-aligned biomimetic fish proves that the interaction between the flow fields induced by the two fish bodies becomes increasingly significant when decreasing the lateral spacing from <semantics>1.4L</semantics> to <semantics>0.6L</semantics>. Notably, an initial lateral convergence of the fish bodies is observed, followed by a sideways swimming pattern at a particular pitch angle, accompanied by a decrement in their forward swimming velocity as they approach each other. Additionally, this study compares flow field alterations in parallel-aligned biomimetic fish with identical lateral spacing but opposing flapping phases. The findings indicate that, irrespective of the phase, the fish exhibit an initial convergence followed by a sideways motion at a specific pitch angle. However, due to disparities in the tail’s flow field, a larger pitch angle is generated when the fish swim in unison. All the findings above will provide a solid theoretical foundation for the design and optimization of underwater robotic vehicles.